Patient-Reported Outcomes in First-Line Antiretroviral Therapy: Results From NEAT001/ANRS143 Trial Comparing Darunavir/Ritonavir in Combination With Tenofovir/Emtricitabine or Raltegravir. (1st December 2018) - George, Elizabeth C.; Bucciardini, Raffaella; Richert, Laura; Dedes, Nikos; Fragola, Vincenzo; Nieuwkerk, Pythia; Spire, Bruno; Volny-Anne, Alain; West, Brian; Molina, Jean-Michel; Horban, Andrzej; Fox, Julie; et al.
Abstract : Background: There are few data comparing patient-reported outcomes (PROs) in randomized trials of initial antiretroviral therapy. We present results from a substudy of the NEAT001/ANRS143 trial. Methods: The randomized trial compared first-line DRV/r 800/100 mg once daily plus RAL 400 mg twice daily and DRV/r plus TDF/FTC 245/200 mg once daily. Changes in PROs were assessed with 3 questionnaires: EuroQoL 5 domains (EQ-5D), Center for Epidemiologic Studies Depression (CES-D) scale, and HIV Treatment Satisfaction Questionnaire. Major depressive disorder (MDD) was defined as CES-D ≥ 16. General estimating equations were used to model change over 96 weeks in PROs from baseline. Results: Of the 805 participants, 797 (99%) contributed to the substudy. Baseline PRO data were similar for the 2 randomized groups. Health status improved over time with a mean increase in EQ-5D visual analogue scale (VAS) of 8.0 by W96 [95% confidence interval (CI): 6.5 to 9.4; P < 0.001], and no statistically significant differences between groups (difference of 0.3 on VAS score (95% CI: −1.7 to 2.3); P = 0.7, global P value ≥0.05 for all domains over follow-up). There was no significant difference between groups on CES-D [difference of −0.1 (95% CI: −1.3 to 1.1); P = 0.9], or MDD during follow-up, adjusted for baseline MDD (odds ratio = 0.98, 95% CI: 0.82 to 1.18; P = 0.9). RAL + DRV/r group had lower level of convenience ( P = 0.03) and fitted less well into patients' lifestyle ( P = 0.007) than the TDF/FTC + DRV/r regimen, and was associated with lower treatment satisfaction [median score: 53 RAL + DRV/r vs 55 TDF/FTC + DRV/r ( P = 0.001)]. Conclusion: PROs improved after starting antiretroviral therapy, with no statistically significant difference between groups. The lower satisfaction with RAL + DRV/r may be explained by twice-daily administration. Abstract : Supplemental Digital Content is Available in the Text.